Tipologi Inovasi Sektor Publik (Program Si-Cakep) di Kabupaten Wajo, Sulawesi Selatan - Yayuk Basuki; Rulinawaty Kasmad; Nasrulhaq Nasrulhaq (Matra Pembaruan: Jurnal Inovasi Kebijakan, 2018)
In order to realize a more quality public service, the Wajo Regency government, namely the Human Resources Development and Personnel Agency (BKPSDM) made an innovation in the field of staffing through the SI-CAKEP Mobile application. This Mobile SI-CAKEP is one of the steps taken to make it easier for the State Civil Apparatus so that they do not have to leave their workplace when they are going to take care of their employment rights, only need to open the application and upload the files needed. As a new application Mobile SI-CAKEP has been included in the Top 99 National Public Service Innovations so it is not wrong to become one of the leading innovations. Therefore, the purpose of this study was to find out the typology of public sector innovation (case study of the SI-CAKEP Mobile program innovation) in Wajo District. The type of research used is a qualitative approach with descriptive research type using a type of case study research that aims to find out more deeply by BKPSDM in making Mobile SI-CAKEP innovations in Wajo District. The result of the study concluded that the innovation of the Mobile SI-CAKEP program is an application that is very helpful for the State Civil Apparatus in fulfilling staffing rights. This application also provides a significant change to staffing services in the human Resources Development ang Human Resources Agency in Wajo District towards a more systematic, integrity, fast, adaptive, commitment, and more professional.